Mapping of ecotourism fitness as a sustainable territorial planning instrument: case study in Brotas municipal, SP - Roque Guerrero, Joao Vitor; Moschini, Luiz Eduardo; Lollo, Jose Augusto de [UNESP]; Tossani de Melo, Naara Aline (Univ Federal Roraima, 2018)
The objective of this study was to apply the mapping of fitness to ecotourism proposed by Aklibasinda and Bulut (2014), in the municipality of Brotas, SP. The methodology aims to analyze aspects of the physical environment and the Land Use from the application of geoenvironmental mapping techniques to determine the potential and restrictions of the site for tourism activities, based on a conservationist bias. For that, geographic data of Precipitation, Land Elevation, Geological Formations of Interest, Proximity of Water Resources, Declivities and Land Use were used. The results obtained show that 83% of the city presents fitness for tourist activities (high or very high), indicating the economic potential that this activity can exert in the municipality and implying the need for public policies for the conservation of natural resources.
Keywords: GIS; Environmental Cartography; Sustainable Tourism